Evaluation of investment decision in ERP/IS - Mohylová, Lucie; Škerlíková, Tatiana; Rudolfová, Lucie; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
This research discusses the financial evaluation of investments in Information Systems (IS) within enterprises. In this research, the focus is on so-called Enterprise Resource Planning (ERP), an IS tool, widely used for decades. In this research, the theory considering ERP will be discussed. In addition to that, theory will be provided about investment rationales of enterprises nowadays. In this case study, the investment in ERP by an enterprise in Czech Republic will be analyzed. The conclusion of this research is based on the researched academic theory and validated by the presented case study. What can be concluded is that current investment evaluation methods for IS investments are only focusing on quantitative easy-to-monetize benefits and costs. However, those do not represent all the considerations that should be made in order to justify the investment. This is because qualitative and indirect benefits are not accounted for in the current evaluation methods.
Vedoucí práce: Tatiana Škerlíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor bakal. práce]; bakalářské práce; bachelor's theses